Desenvolvimento e produtividade da cultura do milho sob diferentes manejos de cobertura, mecanismos sulcadores e velocidades de operação - Trogello, Emerson (2012)
Seeding process is of great importance for annual crops cultivated on no-tillage system since it affects the fitness of the soil around the seed exposing them to adverse conditions what may limit the initial development of plants and minimize the potential yield. In this context, cover plant management may minimize the effectiveness of the planter since conditions provide by the straw sometimes are inadequate for the proper performance of the fertilizer-seeder machines. Associated with this fact, the use of different seed drills and seeding operations at speeds sometimes inadequate may limit crop yield. Following this context, this study aimed to evaluate corn development and productivity submitted to different management methods of cover plants straw, seed drills and speed of operation. The experiment was carried on at the experimental unit of the UTFPR, campus Pato Branco and was laid out in a randomized blocks with split-plot design with 16 treatments and four replications, totaling 64 experimental units. Treatments consisted by the combination of two seed drills (double disc and knife), four managements of cover plants straw (disc, rolled, crushed and desiccated) and two seeding rates (4.5 and 7.0 km h-1) . Soil characterization such as bulk density and mechanical resistance to penetration were evaluated before corn sowing. After the seeding process were evaluated the depth of seed deposition, soil area mobilized, the uniformity of seed distribution and the average number of days for the emergency. Evaluations relating to development and crop yield were performed by measuring the height of plants and height of first ear, percentage of crop cover, initial and final stands of plants, size of ears, number of rows per ear, number of grains per row, thousand grain weight and yield. The data were subjected to analysis of variance and to the significant differences, means were compared by Tukey test at 5% probability. According to the results obtained, it can be concluded that: Seeding operating speed significantly influenced the seeds uniformity of distribution being high values of places without seed and place with two seeds found at the speed of 7.0 km h-1. Furthermore, cover plants straw management significantly influenced the average number of days for plants emergency what result in lower plant height and percentage of coverage by the crop, being the management with plants desiccation the one that showed the lowest values. The treatments used did not influence the corn crop yield components and there was no significant difference to the corn crop yield.